2022
DOI: 10.3390/biom12010076
|View full text |Cite
|
Sign up to set email alerts
|

Calcium Signaling Pathway Is Involved in the Shedding of ACE2 Catalytic Ectodomain: New Insights for Clinical and Therapeutic Applications of ACE2 for COVID-19

Abstract: The angiotensin-converting enzyme 2 (ACE2) is a type I integral membrane that exists in two forms: the first is a transmembrane protein; the second is a soluble catalytic ectodomain of ACE2. The catalytic ectodomain of ACE2 undergoes shedding by a disintegrin and metalloproteinase domain-containing protein 17 (ADAM17), in which calmodulin mediates the calcium signaling pathway that is involved in ACE2 release, resulting in a soluble catalytic ectodomain of ACE2 that can be measured as soluble ACE2 plasma activ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
20
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(22 citation statements)
references
References 102 publications
2
20
0
Order By: Relevance
“…have shown that sACE is promoting rather than inhibiting the entry of the virus in the cells suggesting a proviral role of sACE2 increasing the virus entry ( 34 ). However, in agreement with our other reports it have been shown that sACE2 blocks, rather than enhance, the pseudotyped infection in cell cultures or even SARS-CoV2 infection in cell cultures and animal models ( 35 39 ). The reasons of the possible discrepancies are unknown but could be related to that the pro-infection effect of sACE2 could be relevant in cells/tissues where TMPRSS is not expressed or the different sources of rsACE2 used.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…have shown that sACE is promoting rather than inhibiting the entry of the virus in the cells suggesting a proviral role of sACE2 increasing the virus entry ( 34 ). However, in agreement with our other reports it have been shown that sACE2 blocks, rather than enhance, the pseudotyped infection in cell cultures or even SARS-CoV2 infection in cell cultures and animal models ( 35 39 ). The reasons of the possible discrepancies are unknown but could be related to that the pro-infection effect of sACE2 could be relevant in cells/tissues where TMPRSS is not expressed or the different sources of rsACE2 used.…”
Section: Discussionsupporting
confidence: 93%
“…More importantly, hsACE2 was able to strongly inhibit in vivo (over 90%) SARS-CoV-2 pseudovirus infection and the serum concentrations extrapolated by them ( 40 ) were similar than those described here and presented in our sera. Checking the protective effect of ACE2 would support the utility of soluble ACE2 as a therapy Our results are consistent with the recent results that support use of serum ACE2 as therapy [reviewed in ( 39 )] and clinical trials are underway for rhACE2 ( 41 ).…”
Section: Discussionsupporting
confidence: 89%
“…Kornilov and colleagues have observed that COVID-19-related regulatory pathways may induce ACE2 shedding, and the sACE2 concentrations may correlate with the level of systemic inflammation associated with COVID-19 [ 42 ]. Furthermore, the calmodulin–calcium signaling pathway which contributes to ACE2 release has been suggested to add new insights for clinical/therapeutic applications of ACE2 for COVID-19 [ 43 ].…”
Section: Angiotensin-converting Enzyme 2 (Ace2): the Hottest Target O...mentioning
confidence: 99%
“…Angiotensin-converting enzyme 2, a type I integral membrane protein, acts as a transmembrane protein or a soluble catalytic ectodomain in vivo ( 12 ). The transmembrane ACE2 can be measured as ACE2 expression, and studies indicate that the transmembrane ACE2 is abundant in lungs, heart, and endothelial cells (ECs) ( 13 , 14 ).…”
Section: The Angiotensin-converting Enzyme 2 Receptor and Renin-angio...mentioning
confidence: 99%
“…A disintegrin and metalloproteinase domain-containing protein 17 (ADAM17) mediates cleavage and shedding of the soluble ACE2 ectodomain. ACE2 ectodomain, also known as soluble ACE2, can be detected as plasma ACE2 activity ( 12 ). The soluble ACE2 has been recently recognized to help in controlling SARS-CoV-2 infection via inhibiting their interaction with cell-bound ACE2 ( 17 ).…”
Section: The Angiotensin-converting Enzyme 2 Receptor and Renin-angio...mentioning
confidence: 99%